2021
DOI: 10.1111/bcp.14745
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist‐led intervention on chronic pain management: A systematic review and meta‐analysis

Abstract: Pharmacists have been contributing to the management of chronic pain, ensuring the quality use of medicine. However, there is diversity in the interventions provided by pharmacists and their impact.Methods: Six electronic databases were searched from inception until June 2020 for articles published in English examining the intervention provided by the pharmacist in chronic pain management. Studies investigating the impact of pharmacist intervention individually or multidisciplinary teams including pharmacists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…These pharmacists can help with pain management via medication review, pain assessment, discharge counselling, medication reconciliation, and medication education. 38 …”
Section: Discussionmentioning
confidence: 99%
“…These pharmacists can help with pain management via medication review, pain assessment, discharge counselling, medication reconciliation, and medication education. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses have shown that pharmacists have the potential to effectively manage pain through opioid optimization (Shrestha, Ayesha et al, 2024 ; Shrestha, Kc et al, 2022 ; Thapa et al, 2021 ). Pharmacists play a crucial role in responsible monitoring and the use of opioids to ensure safe and effective pain management while minimising harm such as addiction and overdose.…”
Section: Role Of Pharmacist In Opioid Stewardshipmentioning
confidence: 99%
“…A 2021 systematic review of pharmacy programs for chronic pain identified 14 studies, including six randomised controlled trials, and concluded that pharmacists contributed substantially to the management of chronic pain via improving quality use of medicines and reducing patient pain intensities. However, the evidence for studies which were carried out in hospital outpatient clinics was relatively poor and limited 16 …”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence for studies which were carried out in hospital outpatient clinics was relatively poor and limited. 16 The Society of Hospital Pharmacists of Australia (SHPA) Standard of practice in pain management for pharmacy services 17 recommends that pharmacists in outpatient pain clinics focus resources on identifying patients who are "at risk of medication misadventure, those who have been recently discharged and those who present with persistent pain". 17(p274) In this setting, SHPA provides examples of emerging services which include the triage of high-risk patients for review, increased monitoring and follow-up, and the facilitation of early postdischarge medication review.…”
Section: Introductionmentioning
confidence: 99%